Visitors’ Evaluation Of Facilities And Services At Taman Pertanian Malaysia, Shah Alam, Selangor - Baharuddin, Nor Faeza (2006)

(untitled)
The purpose of this study was to carry out an evaluation of product attributes in Taman Pertanian Malaysia, Shah Alam. This study answered three objectives namely; to examine visitors’ expectation and performance evaluation of the parks’ attribute, to evaluate visitors’ satisfaction of product attributes based on Importance Performance Analysis, and to identify the relationship of the product attributes and overall satisfaction of the visitors. The questionnaires were distributed to visitors selected conveniently at Taman Pertanian Malaysia. A total of 253 questionnaires were completed by the samples involved from which information such as the expectation and performance on selected attributes, demographic characteristics and trip/visiting characteristics were obtained. Overall, this study showed that most of the visitors indicated their dissatisfaction concerning their visit to Taman Pertanian Malaysia. The findings also revealed that three items fell into satisfied attributes (positive disconfirmation), no items in indifferent attributes (confirmation) and fourteen items fell into dissatisfied attributes (negative disconfirmation). Among the 17 attributes that were grouped under the ‘facilities’, ‘services’ and ‘information’ concepts, 82% of the attributes fell into ‘concentrate here’ quadrant and these attributes has need most priorities in terms of improvement. The rest of the attributes were rated as ‘good work’. Apparently, safety and security of visitors attribute were placed high on the visitors list of importance. The model used to evaluate the product attributes in this study proves to be a valid method of measuring recreational satisfaction. Based on the results obtained from this study, it is surmised that the findings and information be appropriately used as guidelines for the management board of the park to help increase visitors’ satisfaction.